Towards sustainable development in industry? reports from seven developing and transition economies - Luken, Ralph Andrew; Hesp, Paul.; Edward Elgar Publishing (Cheltenham ; Northhampton, Mass. : E. Elgar, 2003)
Many developing and transition economies have not yet undertaken the policy integration measures needed to enhance the impact of industry on sustainable development. In this original and insightful book, national experts from Chile, China, the Czech Republic, Pakistan, Tunisia, Turkey and Zimbabwe - countries which all have designated national sustainable development strategies - report on the extent to which recent changes in industrial, environmental and technology policies have more closely aligned industrial development with the aims of sustainable development.
pt. 1. Introduction -- pt. 2. Country reports -- pt. 3. Conclusions.
Includes bibliographical references and index.
Keywords: Sustainable development; Sustainable development -- Developing countries; Industries -- Environmental aspects; Industries -- Environmental aspects -- Developing countries; Industrial policy; Industrial policy -- Developing countries; Environmental policy; Environmental policy -- Developing countries; Electronic books